2006
DOI: 10.2209/tdcpublication.47.117
|View full text |Cite
|
Sign up to set email alerts
|

Morphohistological Change and Expression of HSP70, Osteopontin and Osteocalcin mRNAs in Rat Dental Pulp Cells with Orthodontic Tooth Movement

Abstract: Morphological change and expression of osteopontin, osteocalcin, and HSP70 mRNAs in rat dental pulp cells with experimental orthodontic tooth movement were investigated. Elastic rubber blocks, 0.65 mm in thickness, were inserted between the maxillary first and second molars in rats. In addition to morphological observations of HE staining and TUNEL staining at days 3, 7, 14 and 28 after insertion of elastic rubber blocks, expression of HSP70, osteopontin and osteocalcin mRNAs was also analyzed using quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…Taintor 11) described observation results of vacuolar degeneration of odontoblasts, bulging of micro-vessels, and production of denticles. Shigehara et al 4) have also observed the vacuolar degeneration, a sparse odontoblast layer, and dilation of capillary vessels. The above-mentioned histopathological changes were considered to be caused primarily by alterations in blood vessels in the related periodontal ligament tissue and in those entering the dental pulp 4,11) .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Taintor 11) described observation results of vacuolar degeneration of odontoblasts, bulging of micro-vessels, and production of denticles. Shigehara et al 4) have also observed the vacuolar degeneration, a sparse odontoblast layer, and dilation of capillary vessels. The above-mentioned histopathological changes were considered to be caused primarily by alterations in blood vessels in the related periodontal ligament tissue and in those entering the dental pulp 4,11) .…”
Section: Discussionmentioning
confidence: 93%
“…Tissue changes due to mechanical stress during orthodontic treatment affect not only the above-mentioned tissues, but also the dental pulp [1][2][3] . Shigehara et al 4) demonstrated the expression of osteogenesis-related factors and heat shock protein (HSP) genes in animals. Using Waldo's method 5) from 3 days up to 14 days after the application, they concluded that orthodontic tooth movement causes degenerative changes and apoptosis in the dental pulp cells, while pulp homeostasis is maintained at the genetic level 4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on orthodontic tooth movement in rat demonstrated that mRNA expression of HSP70 in pulp cells was higher in the experimental group than in the control group at all time points. These results suggest that orthodontic tooth movement causes degenerative changes and apoptosis in pulp cells, while pulp homeostasis is maintained at the genetic level 16) . Our results showing increased expression of HSP70 mRNA acting on inhibition of apoptosis sug-gest that HSP70 protects PDL cells undergoing mechanical stress and contributes to maintenance of PDL homeostasis.…”
Section: Discussionmentioning
confidence: 86%
“…genesis [3][4][5][7][8][9][12][13][14][17][18][19][21][22][23][24][25] , that HSP70 was involved in homeostasis 1,16) , and that bFGF was closely involved in both functions 11,18,20) . Although the magnitude of human bite force varies, 500-3,000 g was selected as the standard force for clinical studies 2) .…”
Section: Discussionmentioning
confidence: 99%